1989
DOI: 10.1002/clc.4960120503
|View full text |Cite
|
Sign up to set email alerts
|

Nicardipine, a new calcium channel blocker: Role for vascular selectivity

Abstract: Summary: Calcium channel blockers are important drugs for the treatment of chronic stable angina. However, negative inotropic and dromotropic effects may limit their usefulness in patients with atrioventricular conduction abnormalities or left ventricular dysfunction. A new generation of calcium channel blockers will soon be available that have a more vascular selective action than currently available agents. Of the new agents, nicardipine has been most extensively studied. In experimental studies, nicardipine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Its administration in intravenous form, rapid onset of action and short half‐life allow easy titration against blood pressure while transplacental passage is limited (15%). Nicardipine induces general arterial relaxation that is more pronounced in cerebrovascular and coronary arteries. The depressant action on myocardial muscle cells is less than with nifedipine and its cerebrovascular selectivity renders it more effective in preventing ischemic stroke and hypertensive brain damage than other antihypertensive drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Its administration in intravenous form, rapid onset of action and short half‐life allow easy titration against blood pressure while transplacental passage is limited (15%). Nicardipine induces general arterial relaxation that is more pronounced in cerebrovascular and coronary arteries. The depressant action on myocardial muscle cells is less than with nifedipine and its cerebrovascular selectivity renders it more effective in preventing ischemic stroke and hypertensive brain damage than other antihypertensive drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Nicardipine, like other calcium channel blockers, has the additional advantage of not having the tolerance, which occurs with round-the-clock nitroglycerin. Reduction in afterload caused by the peripheral vasodilating effects may also reduce symptomatic anginal episodes (2,12,14,15). One study also suggested that nicardipine may be effective in reducing the diastolic dysfunction, and potentially the in-creased workload, that can occur with angina (14).…”
Section: Discussionmentioning
confidence: 96%
“…Nicardipine hydrochloride is a second-generation dihydropyridine calcium channel blocker with little effect on myocardial contractility or conduction (1,2) that has been shown to be effective for treating chronic stable angina (3)(4)(5)(6) in several short-term studies. Although previous studies (7,8) do suggest long-term efficacy of nicardipine for the reduction of anginal symptoms, the open-label design did not exclude spontaneous improvement of anginal symptoms or an exercise training effect in the change in symptoms or improvement on exercise parameters (9,10).…”
mentioning
confidence: 99%
“…Prior studies have revealed the safety and efficacy of nicardipine during long-term use [8]. The hypotensive effect of this drug is correlated with initial blood pressure, permitting its administration to normotensive subjects with coronary artery disease as well as to subjects with mild to moderate arterial hypertension [8,9]. The duration of nicardipine therapy required to obtain a clinical reflection of its vascular hyperplasia-preventing effect and whether its chronic use would be followed by the development of tolerance to this beneficial effect remain to be determined.…”
Section: Discussionmentioning
confidence: 99%